1991
DOI: 10.1099/00222615-34-6-355
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of transparent and opaque colony types of Neisseria gonorrhoeae for the genital tract of mice

Abstract: Summary. The virulence of transparent (Tr) and opaque (Op) colony types of Neisseria gonorrhoeae in the genital tract of female mice was evaluated at two stages of oestrous. Isogenic pairs of Tr and Op variants were isolated from N . gonorrhoeae strain 57-120. Both variants exhibited a T2 morphology, but only the Op variant possessed protein I1 (P. 11) in outer-membrane fractions. When administered by intravaginal inoculation Op gonococci were highly infective only for mice in late pro-oestrous, whereas Tr gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Consistent with our observation, Kita et al reported changes in Opa phenotype with respect to the estrous cycle in experimentally infected SLC:ddY mice (35). These observations are consistent with the reported recovery of mostly opaque isolates and of transparent isolates from women in the proliferative and luteal phases of the menstrual cycle, respectively (26,27).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our observation, Kita et al reported changes in Opa phenotype with respect to the estrous cycle in experimentally infected SLC:ddY mice (35). These observations are consistent with the reported recovery of mostly opaque isolates and of transparent isolates from women in the proliferative and luteal phases of the menstrual cycle, respectively (26,27).…”
Section: Discussionsupporting
confidence: 93%
“…Changes in the number of units of this pentameric repeat can cause frameshifts, and consequently the proteins are either correctly translated (phenotype ON) or not correctly translated (phenotype OFF) in different cells of the population (123) (Figure 5). This ON/OFF switching of phenotype occurs during infection and is believed to create variants in the bacterial population capable of surviving in the host (61). Other compelling examples come from Haemophilus influenzae, in which the outer membrane structure is also phase variable.…”
Section: Phase Variations In Host-adapted Prokaryotesmentioning
confidence: 98%
“…In the bacterium, Neisseria gonorrhoeae , repeat variations in the P. II family of cell surface genes allow for evasion of the host immune system [54]. Changes in the CTCTT pentameric microsatellite repeat in the coding region of the membrane signal peptide of cell surface genes, can either lead to correct or incorrect translation of proteins [55].…”
Section: Repeats In Coding Regionsmentioning
confidence: 99%